UJI KADAR ABU LARUT AIR DAN KADAR ABU TIDAK LARUT ASAM PADA SIMPLISIA BIJI JAMBU BOL (Sygyzium malaccense) - Rosa Devitria; Resti Wulandari; Mega Elfia (LPPM Universitas Abdurrab, 2023)
Guava (Syzygium malaccense) is an annual fruit plant of the guava family. The guava fruit has a softer and denser flesh texture compared to other guavas. Guava contains a lot of substances that are very good for the health of the body. Among them are fiber, potassium, phosphorus, vitamin A, vitamin B1, vitamin C, thiamine, riboflavin, ascorbic acid, and niacin. Guava fruit (S. malaccense) has high anti-inflammatory antioxidant activity. Guava leaf extract (Sygygium malaccense) also exhibits antioxidant, anti-inflammatory and anti-diabetic cytotoxic properties. Guava (S. malaccense) bark extract has the effect of lowering sugar levels and cholesterol levels. The root of the guava tree is often used to treat itching, as a diuretic and to relieve edema. The purpose of this research was to determine the water-soluble ash content and acid insoluble ash content in guava seed samples. The method used is random sampling. From the results of the simplicia standard determination, the water-soluble ash content is 0.01% and the acid insoluble ash content is 0.37%, indicating the results are in accordance with the requirements in (SNI 2886: 2015). Conclusion Based on the results obtained from research on the water-soluble ash test and acid insoluble ash test using guava seed simplicia obtained from 10 grams of simplicia each, the results of the determination of water-soluble ash content are 0.01% according to SNI 2886:2015, and the determination of the acid insoluble ash content of 0.37% is not in accordance with SNI 2886:2015